Parasocial politics : audiences, pop pulture, and politics - Zenor, Jason (Lexington Books, 2014)
Parasocial Politics explores how consumers form complex relationships with media texts and characters, and how these readings exist in the nexus between the real and fictional worlds. This collection of empirical studies analyzes how actual consumers read the text and the overt and covert political messages encoded in popular culture.